2022
DOI: 10.2196/33911
|View full text |Cite
|
Sign up to set email alerts
|

Digital Facilitation to Support Patient Access to Web-Based Primary Care Services: Scoping Literature Review

Abstract: Background The use of web-based services within primary care (PC) in the National Health Service in England is increasing, with medically underserved populations being less likely to engage with web-based services than other patient groups. Digital facilitation—referring to a range of processes, procedures, and personnel that seek to support patients in the uptake and use of web-based services—may be a way of addressing these challenges. However, the models and impact of digital facilitation curren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 100 publications
(278 reference statements)
1
11
0
Order By: Relevance
“…A recent systematic review of approaches to digital facilitation in primary care suggests that low knowledge of which web-based services are available is a significant barrier to their use in primary care [ 9 ]. Training and education, for instance, through web-based videos or in-person seminars, may promote the uptake and use of digital services [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review of approaches to digital facilitation in primary care suggests that low knowledge of which web-based services are available is a significant barrier to their use in primary care [ 9 ]. Training and education, for instance, through web-based videos or in-person seminars, may promote the uptake and use of digital services [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of approaches to digital facilitation in primary care suggests that low knowledge of which web-based services are available is a significant barrier to their use in primary care [ 9 ]. Training and education, for instance, through web-based videos or in-person seminars, may promote the uptake and use of digital services [ 9 ]. Some of the respondents in our study described needing support to access online services, and previous research has suggested that patient-centred guidance and practice champions as ‘experts’ may increase initial uptake or support continued use of web-based services [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital health techniques can reduce inequalities in access to health care and allow health care centers at different levels of care to co-operate for better and effective health care management of patients [ 20 , 27 ]. This study might help to clarify whether telemedicine-assisted ultrasound by a qualified expert is non-inferior to in-presence sonography (by a qualified expert) concerning clinical success.…”
Section: Discussionmentioning
confidence: 99%
“…The scoping review was conducted in stages (Figure 1) to allow learning from earlier stages to be fed into later stages. The protocol for the study was registered with PROSPERO (International Prospective Register of Systematic Reviews; registration number CRD42020189019) [25].…”
Section: Overviewmentioning
confidence: 99%